2011
DOI: 10.1177/0310057x1103900115
|View full text |Cite
|
Sign up to set email alerts
|

Post-Craniotomy Pain in a Paediatric Population

Abstract: There is little information about analgesia use or pain experienced in children after neurosurgery. The aims of this study were to assess the degree of pain experienced by children after neurosurgery and the analgesic regimens used, and to identify factors associated with significant pain. Data for 52 children who underwent craniotomy were collected contemporaneously over 72 hours. Data included demographics, intraoperative surgical and anaesthetic details, postoperative medications and postoperative pain scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
1
28
1
3
Order By: Relevance
“…There are limited data describing the incidence of pain and the effects of treatment after neurosurgery in children. A single‐centre cohort study evaluating 52 children who underwent craniotomy reported that the majority of pediatric neurosurgical patients complained of little pain in the setting of substantial multimodal postoperative therapy including parenteral strong opioids . This study also found that older age and longer procedures were associated with increased pain after intracranial surgery.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…There are limited data describing the incidence of pain and the effects of treatment after neurosurgery in children. A single‐centre cohort study evaluating 52 children who underwent craniotomy reported that the majority of pediatric neurosurgical patients complained of little pain in the setting of substantial multimodal postoperative therapy including parenteral strong opioids . This study also found that older age and longer procedures were associated with increased pain after intracranial surgery.…”
Section: Introductionmentioning
confidence: 74%
“…One can hypothesize that an increased surgical length may produce longer central nervous system stimulation and thus wind up of pain pathways. Furthermore, it was previously reported that a long surgical procedure is associated with an increase in morphine consumption after major craniotomy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies of any size have focused specifically on the incidence and severity of postoperative pain in pediatric patients after cranial surgery or on how this pain is treated . In adult populations, some investigators have questioned the need for analgesia, believing pain was minimal, whereas others recommended PCA .…”
Section: Discussionmentioning
confidence: 99%
“…There have been few studies comparing standard analgesic regimens. Opioids: the use of parenteral opioids following craniotomy and major neurosurgery has been described (387)(388)(389)(390). PCA with fentanyl plus a continuous infusion of midazolam has been described (391).…”
Section: Evidencementioning
confidence: 99%